Introduction to the Aesthetic Aspects of the Slovak Left-Wing Revue DAV - PERNÝ, Lukáš Perný (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2022)
DAV (based on the initials of the first names of Daniel Okáli, Andrej Sirácky, and Vladimr Clementis) was a leftist journal produced by the group Davisti (young, left-wing Czecho-Slovak intellectuals) in Prague and Bratislava between 1924 and 1937, with intervals. The DAV group was not a writers’ club but rather a free association of authors who rejected Nazism during World War II. The DAV group discussed art, philosophy, literature, criticism, politics, and other topics. The Davists, through the DAV revue, influenced the development of Marxism in Slovakia. The DAV revue was also influential in establishing modernist trends in Slovak visual art and literature. The presented text expands on the short encyclopaedia article “DAV (The Crowd) – Slovak left-wing avant-garde group of the interwar period” (2021) and puts it into aesthetic contexts. This work used the context of Slovak aesthetician J. Migašová’s work (a study on the influence of the New Objectivity and artistic modernity on socially critical art in interwar Slovakia) and M. Habaj’s aesthetical analysis to analyse the first two issues of the DAV revue. This study primarily concentrated on the DAV revue’s representations of typical Slovak artistic modernism.